Molecular insights into the mechanism of sugar-modified enkephalin binding to opioid receptors. (December 2022) - Ślusarz, Magdalena J.
Abstract: Opioid receptors (delta, kappa, and mu) belong to the G protein-coupled receptor (GPCR) superfamily. They are responsible for pain perception - being activated by opioid peptides such as enkephalins, endorphins and dynorphins and by opiates, such as morphine. Enkephalins are naturally occurring endogenous pentapeptides with the amino acid sequence Tyr-Gly-Gly-Phe-Leu/Met. Both enkephalins are potent agonists of the delta receptor, and to a lesser extent the mu receptor, with little to no effect on the kappa receptor. Like most small peptides, enkephalins are easily catabolised via enzymatic degradation and show poor blood-brain barrier penetration. The attachment of sugars to peptides increases their penetration of the blood-brain barrier but also may affect interactions with receptors. In this study, the [Leu 5 ]enkephalin and [Leu 5 ]enkephalin containing the β-D -glucuronic acid were investigated to explain how the presence of sugar moiety in the peptide molecule influences its interaction with the opioid receptors. In conclusion, the conjugation of an enkephalin molecule with the glucuronic acid has a direct and strong impact on the receptor-ligand interactions. The enhancement of ligand binding is much stronger in the delta receptor than in the mu receptor; thus, enkephalin conjugated with glucuronic acid shows greater selectivity toward the delta opioid receptor than the original peptide. Graphical Abstract: ga1 Highlights: Enkephalins are naturally occurring endogenous peptides that act as agonists of opioid receptors. Molecular dynamics has been performed to determine the receptor-ligand binding mode. The conjugation of an enkephalin molecule with glucuronic acid has a direct impact on the receptor-ligand interactions. Strong polar interactions at the enkephalin termini anchor the ligand to the receptor and are crucial for agonist activity.